PENGARUH PROFITABILITAS, LIKUIDITAS, FIRM GROWTH, KEBIJAKAN DEVIDEN DAN TAX AVOIDANCE TERHADAP NILAI PERUSAHAAN : (Studi Pada Sektor Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2016-2019) - Suratman Suratman; Nanang Ari Utomo (Pusat Riset dan Inovasi Nasional, 2021)
The purpose of this study was to determine the effect of profitability, liquidity, company growth, dividend policy and tax avoidance (study on the manufacturing sector listed on the Indonesia Stock Exchange). The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2019 period, totaling 76 companies. The data collection method used in this research is documentation. The source of data in this study is secondary data in the form of financial reports published on the Indonesia Stock Exchange (IDX). The data analysis technique used was multiple linear regression which was preceded by classical assumption test consisting of normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. While hypothesis testing is done by using the coefficient of determination, t test and F test. In this study, the results of the analysis show that profitability has effect on firm value, liquidity has no effect on firm value, firm growth has no effect on firm value, dividend policy has effect on firm value, and tax avoidance has effect on firm value.